How anatomical asymmetry of human auditory cortex can lead to a rightward bias in auditory evoked fields - Shaw, Marnie; Hämäläinen, Matti; Gutschalk, Alexander (NeuroImage, 2013)
Auditory evoked fields and potentials, such as the N1 or the 40-Hz steady state response, are often stronger in the right compared to the left auditory cortex. Here we investigated whether a greater degree of cortical folding in left auditory cortex could result in increased MEG signal cancelation and a subsequent bias in MEG auditory signals toward the right hemisphere. Signal cancelation, due to non-uniformity of the orientations of underlying neural currents, affects MEG and EEG signals generated by any neuronal activity of reasonable spatial extent. We simulated MEG signals in patches of auditory cortex in seventeen subjects, and measured the relationships between underlying activity distribution, cortical non-uniformity, signal cancelation and resulting (fitted) dipole strength and position. Our results suggest that the cancelation of MEG signals from auditory cortex is asymmetric, due to underlying anatomy, and this asymmetry may result in a rightward bias in measurable dipole amplitudes. The effect was significant across all auditory areas tested, with the exception of planum temporale. Importantly, we also show how the rightward bias could be partially or completely offset by increased cortical area, and therefore increased cortical activity, on the left side. We suggest that auditory researchers are aware of the impact of cancelation and its resulting rightward bias in signal strength from auditory cortex. These findings are important for studies seeking functional hemispheric specialization in the auditory cortex with MEG as well as for integration of MEG with other imaging modalities.
Available online 13 February 2013
Gesehen am 24.10.2022